Exploring innovation in the development of teaching aids among prospective teachers for the implementation of assessment of reading skills - Jamil, Halimah (Macrothink Institute, 2024)
The use of teaching aids during the teaching and learning process (T&L) is very important for teachers to ensure that the delivery of information related to the subjects taught is more clear, systematic and can be followed by students better. Educators of the 21st century are advised to innovate in developing teaching aids to improve in the Malay language skills continuously as contained in the Malaysian Education Development Plan (PPPM) 2013-2025. The research question of this study is i) what kind of teaching aids are developed by prospective teachers in teaching and learning Malay language?, ii) what is the challenge of developing innovative teaching aids among prospective teachers for teaching and learning the Malay language, and iii) what are the skills of innovation in the development of teaching aids among prospective teachers for teaching and learning the Malay language?. The qualitative survey involved a total of seven prospective Malay Language teachers. The results of the study through interviews and observations found that the development of teaching aids showed that the participants have high skills and knowledge, the participants have creative and innovative skills by combining various materials, can move the T&L process more effectively in developing teaching aids for Malay language and Malay literature. The results of teaching aids innovations that they develop help students to easily understand the topics taught in class. The diversity in the selection of teaching aids in this study can be applied to other subjects in future studies.